KONSEP PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH RENCANA DETAIL TATA RUANG DAN KAWASAN - Tomy M Saragih (SASI, 2011)
Organizing public participation in spatial planning becomes very important and needs to be considered in the process of spatial planning, both in the planning process, utilization, space utilization and control to minimize conflicts between interested parties.